An Analysis of Figurative Language Used in Nine Track Mind Album by Charlie Puth - Novita Dewi, Sintana; Ida Ayu Putri Gita Ardiantari (Prodi Sastra Inggris Fakultas Bahasa Asing Universitas Mahasaraswati Denpasar, 2024)
In writing songs, songwriters often use figurative language. In this study, analyzed the figurative language contained in the album Nine Track Mind by Charlie Puth. The purpose of this study was to determine the type of figurative language used and the meaning shown by figurative language in the songs on the album. This research is a descriptive research with qualitative and quantitative approaches. The data found on this research were analysed by theory of Knickerbocker and Reninger (1963) and supported by the theory of Wellen and Warren (1984). The results of this study showed that there were ten figurative languages used by songwriters, namely 60% hyperbole, 10% allusion, 10% repetition, 20% metaphor. In addition, the songwriter also uses connotative and denotative meanings in the album. Keywords: figurative language, song, album.